2010
DOI: 10.20882/adicciones.207
|View full text |Cite
|
Sign up to set email alerts
|

Trastornos de personalidad en fumadores: una revisión

Abstract: The association between psychopathology and nicotine dependence in smokers has been a relevant topic in recent years. Nevertheless, little is known about personality disorders in smokers. The aim of this article is to review research published nationally and internationally which analyzes the relation between tobacco use and personality disorders. Our review permits us to affirm that research on the presence of Axis II disorders in smokers is rather scarce. Of 12 studies analyzed, it can be concluded that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
1
0
1
Order By: Relevance
“…As predictable, it has been suggested that the change in these patterns affects some of the consumption behaviors. A study on student population demonstrated that decreasing neuroticism and impulsivity correlates with decreased substance involvement during emerging adulthood ( 19 ). We found that depressive personality increases the likelihood of regular smoking by 2.8 times and histrionic personality increases the chance of smoking, either as an experimenter or as a regular smoker, by 2.2 times.…”
Section: Discussionmentioning
confidence: 99%
“…As predictable, it has been suggested that the change in these patterns affects some of the consumption behaviors. A study on student population demonstrated that decreasing neuroticism and impulsivity correlates with decreased substance involvement during emerging adulthood ( 19 ). We found that depressive personality increases the likelihood of regular smoking by 2.8 times and histrionic personality increases the chance of smoking, either as an experimenter or as a regular smoker, by 2.2 times.…”
Section: Discussionmentioning
confidence: 99%
“…Junto a estos factores sociales, se ha asociado a menudo el consumo de tabaco a los estados depresivos y estados de ánimo negativos (Becoña y Míguez, 2004;Becoña, Vázquez y Míguez, 2002;Fernandez del Río y Becoña, 2009;Groth y Morrison-Beedy, 2011). Al respecto, hay que destacar las evidencias que acreditan la bidireccionalidad de este factor de riesgo: el consumo habitual de tabaco es también un factor de riesgo en la aparición de estados de ánimo negativos y síntomas de tipo depresivo-ansioso (Breslau, Kilbery y Andreski, 1993;Breslau, Peterson, Schultz, Chilcoat y Andreski, 1998;Colvin y Mermelstein, 2010;Fergusson, Lynskey y Horwood, 1996;Parrott y Garnham, 1998;Piasecki, 2000).…”
unclassified